Modelling the sustainability of public sector debt and net foreign asset positions - Ong, Kian H. (2016)
The European Sovereign Debt crisis in 2010 not only brings the sustainability of public finance to the forefront, but also the sustainability of external balances. Chapter 2 of this thesis proposes an approach to measuring fiscal sustainability of a country; Chapter 3 investigates the divergent external imbalances in Europe, and Chapter 4 proposes the measures of external sustainability for a country.